Pimpinella anisum in modifying the quality of life in patients with functional dyspepsia: A double-blind randomized clinical trial - S Ashraffodin Ghoshegir; Mohammad Mazaheri; Alireza Ghannadi; Awat Feizi; Mahmoud Babaeian; Maryam Tanhaee; Mehrdad Karimi; Peyman Adibi (Journal of Research in Medical Sciences, 2014)
Background: We aimed to assess the effects of anise on quality of life (QOL) of patients with functional dyspepsia (FD) in a double-blind randomized clinical trial. Materials and Methods: Of 180 patients attending the gastroenterology clinic, 107 ones with the diagnosis of postprandial distress syndrome according to Rome III criteria were enrolled. They were randomized into two groups, anise and placebo. Anise group involved 47 patients and received anise powders, 3 g after each meal (3 times/day) for 4 weeks. Control group had 60 patients who received placebo powders (cornstarch), 3 g after each meal (3 times/day) for 4 weeks. The QOL was assessed by short-form (SF)-36 questionnaire. Mean scores of eight health domains of the two groups were compared at baseline and at the end of study. Results: The age, sex, body mass index, smoking history, tea and coffee drinking patterns of the two groups were not significantly different. All domains of SF-36 were similar between the two groups at baseline but were significantly different at week 12. At baseline, mean score of physical component summary was 159 in placebo group and 167 in anise group (P = 0.1). At week 12, the score was 141 in placebo group and 251 in anise group (P = 0.0001). Mean baseline score of mental component summary was 172 and 165 in placebo and anise groups, respectively (P = 0.1). At week 12, the score was 135 in placebo group and 233 in anise group (P = 0.0001). Conclusion: The current study revealed the effectiveness of anise in improvement of QOL in patients with FD.